Better thermal management options with heat storage systems for various applications: An Evaluation. Issue 1 (29th April 2019) - Acar, Canan; Dincer, Ibrahim
Abstract: With increasing worldwide population and rising standards of living, the global energy consumption is increasing at significant rates. Together with climate change concerns and negative impacts of fossil fuel use, the need for clean and smart energy systems is becoming more obvious. Clean and smart systems provide energy to all types of end‐use applications in an environmentally friendly, affordable, reliable, and efficient manner. Heat losses are recognized as some of the most significant causes of efficiency degradation in energy systems. Therefore, this study overviews and investigates current and future thermal management options for different end‐use purposes for a more sustainable future. In this study, a smart approach is taken when evaluating existing and emerging thermal management systems and smart targets are introduced for better thermal management systems. In addition, some novel thermal management systems for various applications such as electric/hybrid vehicles, power systems, and industrial processes are introduced as case studies and the energy and exergy efficiencies of these case studies are compared. In addition, some key future directions are provided in terms of better thermal management options for a sustainable future. The case study results of this study show that with better thermal management strategies, it is possible to reach energy and exergy efficiencies up to 60% and 50%, respectively in hybrid vehicles, industrial processes, and robotic applications.